Falling Into the Second-Generation Decline? Evidence From the Intergenerational Differences in Social Identity of Rural–Urban Migrants in China - Leng, Xiangming; Zhong, Min; Xu, Junling; Xie, Shenghua (SAGE open, 2020)
Previous studies have not adequately articulated the intergenerational differences in social identity of rural–urban migrants in China. Using survey data from Wuhan, China, the study tests three hypotheses on intergenerational differences in rural–urban migrants’ social identity based on first-generation and new-generation migrants’ attitudes toward rural and urban society. Results suggest that first-generation migrants are more likely to view themselves as rural rather than urban citizens. However, new-generation migrants tend to regard themselves as neither peasants nor urban citizens, which means that their identity reconstruction is at a stalled status. The identity perplexity of new-generation migrants suggests that they may be in danger of falling into the second-generation decline because there is a mismatch between their aspirations and the practical situation of their identity integration. This article highlights that when analyzing rural–urban migrants’ social identity, it is very important to consider the role of generation and rural–urban migrants’ attitudes toward their background society. Furthermore, the study suggests that in a rural–urban dichotomized society without institutional and social support, rural–urban migrants’ identity integration will not be achieved. Therefore, the Chinese government needs to build an institutionally and socially inclusive society.